The genetic characterization of grapevines prospected in old Serbian vineyards reveals multiple relationships between traditional varieties of the Balkans - Tello, Javier; Todić, Slavica; Ferradás, Yolanda; Nikolic, Miroslav; Sabovljević, Aneta; Ivanišević, Dragoslav; Tomanović, Željko; Grbić, Miodrag; Martínez-Zapater, José Miguel; Ibáñez, Javier (Frontiers in Plant Science, 2024)
Serbia preserves a high number of local grape varieties, which have been cultivated across the country for centuries. Now, these ancient varieties are in the spotlight, and there is a global trend towards their recovery and characterization because they can revitalize regional, national and international grape and wine sectors. In addition, their genetic study can be useful to find new pedigree relationships to reveal how local varietal assortment evolved over time. Here, the genetic characterization of 138 grapevines from old Serbian vineyards revealed 59 different genetic profiles, 49 of which were identified as grapevine varieties whose origin in the country could be linked to some major Serbian historical periods. Most of the genetic profiles found in this work arranged in a complex pedigree network that integrates numerous grapevine varieties from diverse Balkan countries, agreeing with an intense exchange of plant material among Balkan regions for centuries. This analysis identified some varieties as important founders of Balkan genetic resources, like ‘Alba Imputotato’, ‘Braghina Rosie’, ‘Coarna Alba’, and ‘Vulpea’. After deepening into their genealogy, these major direct founders might have ultimately derived from ‘Visparola’, an ancient variety of likely Balkan origin with a major founding role in some European regions. Our results also indicated the genetic singularity of the grapevine resources from the Balkans when compared to those from other relevant winemaking regions, supporting the interest of their detailed study to evaluate their oenological potential and for the eventual identification of useful traits to counteract current viticulture challenges.